Analisis Laju Korosi Dan Maximum Allowable Working Pressure (Mawp) Pada Jaringan Pipa Hydrant - Soleh Sabarudin, Moh; Indra Chandra Setiawan (Teknobiz : Jurnal Ilmiah Program Studi Magister Teknik Mesin, 2025)
Development in urban areas is increasingly developing, with various designations, various buildings are built to meet the needs of human life. With the continued growth of gedeung buildings in cities, the availability of land is increasingly expensive because it is limited. High-rise buildings are one of the solutions to this problem, with multi-storey buildings with limited land can get large functions according to the needs of the building designation. The tall building that we usually call a High Risk Building is growing rapidly with the concept of design and construction built with various characters and technological sophistication in it. The building safety system against fire hazards that we know as the Fire Figthing System is one of the systems that must be present in high-rise buildings and one of them is the hydrant system in high-rise buildings. Hydrants must be designed in accordance with existing standards and regulations such as the National Fire Fighting Association (NFPA), SNI, local regulations and other government regulations. With the pressure on the hydrant pipeline network, carbon steel pipes are an option, with water fluid as a standby extinguishing medium in the carbon steel pipeline network, the potential that occurs is corrosion. In the installed hydraulic pipe network already has an installed life of approximately 15 years, then corrosion must occur, with the measurement method using UTM (Ultrasonic Thickness Measurement) the thickness of the existing pipe can be determined. So that it can be calculated whether the corroded pipe network is still safe to use or needs to be replaced with a new pipe. The surface morphology and corrosion products are characterized using Scanning Electron Microscopy (SEM), and Dispersive X-ray Energy (EDX) to determine the characterization of the corrosion process and the elements that cause the corrosion. With a series of checks and calculations of the Maximum Allowable Working Pressure (MAWP) on the hydrant pipeline network, it will be answered whether the installed hydrant pipeline network can still withstand internal pressure.